تحديد العوامل المؤثرة على محتوى الخبز المنتج في المنطقة الساحلية من مادتي الألياف والبروتين - قرحيلي, ياسر; معروف, نجمة (Latakia University Journal -Biological Sciences Series, 2014)
لقد سحبت عينات عشوائية من أنواع الخبز المستهلكة في المنطقة الساحلية خلال سنوات البحث, وحسبت نسبة الألياف والبروتينات فيها, ودرس تأثير الخلطة المعتمدة بشكل سنوي في المطاحن على محتوى الدقيق التمويني من الألياف والبروتينات. لقد أظهرت الدراسة الدور الهام لهذه الخلطة, حيث ارتفعت نسبة الألياف من (1.06%) في 2009 إلى (1.61%) في 2010, وارتفعت نسبة البروتين ايضا من (11.36%) عام 2010 إلى (13.90%) عام 2012, وتبين أنه هناك بعض المطاحن الحكومية وليست كلها تقوم بإضافة النخالة الناعمة الغنية بالألياف والبروتين إلى الدقيق, دون إغفال أثر العمليات التكنولوجية المطبقة خلال مراحل تصنيع الخبز, وخاصة مرحلتي التخمر و الشواء. A random sample of the kinds of bread consumed in the coastal region during the years of research was taken, the percentage of fiber and protein was calculated, and the effect of the mixture approved on an annual basis in mills on purveyance flour content of fiber and protein was studied. The study showed the important role of the mixture, where the percentage of fiber increased from (1.06%) in 2009 to (1.61%) in 2010, and the percentage of protein increased also from (11.36%) in 2010 to (13.90%) in 2012. The results show that there are some, but not all, governmental mills which add soft bran fiber and protein-rich flour, taking into consideration the impact of technological processes applied throughout the stages of manufacturing bread, and in particular the stages of fermentation and broil.